Manual of valvular heart disease - Asher, Craig R.; Griffin, Brian P., 1956- (Wolters Kluwer, 2018)
"Portable and clinically oriented, this full-color handbook is a unique and timely guide to valvular heart disease and percutaneous coronary interventions. A structured, standardized format helps you quickly find the information you need, while numerous illustrations and videos online provide visual support for key concepts and procedures. Key Features: Numerous tables, diagrams, and images highlight concepts, procedures, and devices related to valvular heart disease. Structured outline format lists landmark articles, key reviews, and relevant book chapters at the end of each chapter. Online chapter self-assessment questions and answers allow you to self-test and review key concepts. Authored by current or former Cleveland Clinic trainees and clinicians, as well as international experts in the field. Ideal for interventional cardiologists, fellows, cardiothoracic surgeons, anesthesiologists, cardiac technicians, sonographers, nurses, physician assistants and nurse practitioners. Your book purchase includes a complimentary download of the enhanced eBook for iOS, Android, PC & Mac."--Provided by publisher.